Penerapan Metode Single Exponential Smoothing Dalam Meramalkan Penjualan Sofa Berbasis Web - Masaeni Waruwu (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Aston Furniture is a company engaged in the sale of furniture. The problem that exists in Aston Furniture is that sofa sales data processing still uses a manual system, which still uses notes and bookkeeping as a place to store sofa sales data. A sofa sales forecasting system at Aston Funiture that aims to help speed up searching for sofa sales data and assist in determining sofa sales forecasting for certain periods based on year. This study discusses sofa sales forecasting using UML (Unified Modeling Language) as a tool in analysis and design, as well as the PHP Hypertext Preprocessor programming language with the CodeIgniter framework, and MySQL as the data storage medium. Forecasting calculations are performed using Single Exponential Smoothing, namely using previous sales data by month and year. The result of this research is to produce sofa sales forecasting.